A bidirectional association between smartphone addiction and depression among college students: A cross-lagged panel model - Kexin Zhang; Haiyun Guo; Tianli Wang; Jianghui Zhang; Guojing Yuan; Juan Ren; Xueqing Zhang; Huayu Yang; Xiaoyan Lu; Zhihui Zhu; Jun Du; Haiyan Shi; et al. (Frontiers Media S.A., 2023)
BackgroundSmartphone addiction (SA) is associated with adverse consequences, especially for freshmen. Evidence indicates that SA is associated with depression, and it is necessary to conduct a longitudinal study to explore the association further.MethodsSA (measured by the Smartphone Addiction Scale-Short Version) and depression (measured by the Zung's Self-Rating Depression Scale) among 1,186 freshmen were surveyed at baseline and a respective 12-month follow-up for each participant. The application of a cross-lagged panel model approach (CLPM) revealed an association between SA and depression after adjusting for demographic variables.ResultsThe CLPM results showed a significant path from baseline SA to follow-up depression (β = 0.08, P < 0.001) and a significant path from baseline depression to follow-up SA (β = 0.08, P < 0.001). Compared with the overall cross-lagged model, the cross-lagged coefficient of the path from baseline SA to follow-up depression increased in the female group (β = 0.10, P = 0.015), and the cross-lagged coefficient of the path from baseline depression to follow-up SA also increased significantly (β = 0.15, P < 0.001). In contrast, the cross-lagged model in the male group showed no predictive effect between SA and depression (P > 0.05).ConclusionsThe current study showed a significant bidirectional association between smartphone addiction and depression among freshmen, but only in the female population.